2022
DOI: 10.3389/fimmu.2022.976382
|View full text |Cite
|
Sign up to set email alerts
|

Differences in systemic and mucosal SARS-CoV-2 antibody prevalence in a prospective cohort of Dutch children

Abstract: BackgroundAs SARS-CoV-2 will likely continue to circulate, low-impact methods become more relevant to monitor antibody-mediated immunity. Saliva sampling could provide a non-invasive method with reduced impact on children. Studies reporting on the differences between systemic and mucosal humoral immunity to SARS-CoV-2 are inconsistent in adults and scarce in children. These differences may be further unraveled by exploring associations to demographic and clinical variables.MethodsTo evaluate the use of saliva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Firstly, the percentage of positivity to anti-SARS-CoV-2 N/S IgG was lower in children than in adults. These results are consistent with findings from Keuning et al [ 32 ], who suggested that the elevated prevalence of positivity in serum compared with saliva could be partially explained by time kinetics and demographic differences. Secondly, adult patients reported higher SARS-CoV-2 antibody titers than children in both the salivary and serum samples.…”
Section: Discussionsupporting
confidence: 93%
“…Firstly, the percentage of positivity to anti-SARS-CoV-2 N/S IgG was lower in children than in adults. These results are consistent with findings from Keuning et al [ 32 ], who suggested that the elevated prevalence of positivity in serum compared with saliva could be partially explained by time kinetics and demographic differences. Secondly, adult patients reported higher SARS-CoV-2 antibody titers than children in both the salivary and serum samples.…”
Section: Discussionsupporting
confidence: 93%
“…Virus-specific nasal and saliva antibodies are significantly correlated with each other after SARS-CoV-2 infection [ 26 ]. The correlation between SARS-CoV-2-specific antibodies in serum and saliva was also reported by a cohort study of Dutch children, irrespective of SARS-CoV-2 exposure, symptoms, or vaccinations [ 27 ]. Of note, saliva antibodies decline earlier than serum antibodies in vaccinated and unvaccinated individuals [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 55%
“…Briefly, the quantitative Luminex assay was used to measure S-specific IgG and nucleocapsid (N) specific IgG, with results expressed as international Binding Antibody Units per mL (BAU/ml) ( 21 , 22 ). Participants with S-specific IgG above 44.8 BAU/ml were considered seropositive ( 23 ). Nucleocapsid (N)-specific IgG antibodies were analyzed to identify participants who contracted COVID-19 before or during the study.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleocapsid (N)-specific IgG antibodies were analyzed to identify participants who contracted COVID-19 before or during the study. We selected a cutoff value with 100% specificity, measured in pre-pandemic sera from healthy donors, to minimize the possibility of false-positive results due to administration of (low levels of) N-specific antibodies in IGRT ( 23 , 24 ). Therefore, an infection with SARS-CoV-2 was defined as a history of a positive PCR test, positive antigen test, and/or an N-specific IgG titer above 42.2 BAU/ml.…”
Section: Methodsmentioning
confidence: 99%